Long-term dominance of Mycobacterium tuberculosis Uganda family in peri-urban Kampala-Uganda is not associated with cavitary disease - Wampande, Eddie M.; Mupere, Ezekiel; Debanne, SaraM; Asiimwe, Benon B.; Nsereko, Mary; Mayanja, Harriet; Eisenach, Kathleen; Kaplan, Gilla; Boom, Henry W.; Gagneux, Sebastien; Joloba, Moses L. (BMC Infectious Diseases, 2013)
Previous studies have shown that Mycobacterium tuberculosis (MTB) Uganda family, a sub-lineage of the MTB Lineage 4, is the main cause of tuberculosis (TB) in Uganda. Using a well characterized patient population, this study sought to determine whether there are clinical and patient characteristics associated with the success of the MTB Uganda family in Kampala. A total of 1,746 MTB clinical isolates collected from1992-2009 in a household contact study were genotyped. Genotyping was performed using Single Nucleotide Polymorphic (SNP) markers specific for the MTB Uganda family, other Lineage 4 strains, and Lineage 3, respectively. Out of 1,746 isolates, 1,213 were from patients with detailed clinical data. These data were used to seek associations between MTB lineage/sub-lineage and patient phenotypes.
Keywords: Mycobacterium tuberculosis complex; Lineage; Single nucleotide polymorphism; Mycobacteria; Strain family; Cavitation; Virulence; Epidemiology; Evolution